2005
DOI: 10.1111/j.1559-1816.2005.tb02175.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Affirmative Action: A Comparison of Color-Blind Versus Modern Racist Attitudes

Abstract: In the hotly contested issue of affirmative action, detractors maintain that the use of race‐conscious policies to remedy past discrimination is contraindicative of a color‐blind society. Supporters of affirmative action maintain that while a color‐blind society may be desirable, acts of past discrimination and current institutional racism make it necessary to use race‐conscious policies. Past research has shown that the demographic variables of race and sex, as well as modern racist attitudes predict attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
92
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(104 citation statements)
references
References 29 publications
10
92
0
1
Order By: Relevance
“…Finally, in support of the attitude-behaviour hypothesis (Ajzen & Fishbein, 2005;Glasman & Albarracin, 2006), as well as the findings of previous research (e.g., Awad et al, 2005;Ellis et al, 2002;Kluegel & Smith, 1983), prejudice towards Indigenous Australians was negatively correlated with bystander anti-racism intentions. Those who reported more negative attitudes toward Indigenous Australians indicated that they were less likely to intervene on their behalf when witnessing an instance of discrimination against them.…”
Section: Correlates Of Bystander Anti-racism Intentions (Aim 1)supporting
confidence: 77%
“…Finally, in support of the attitude-behaviour hypothesis (Ajzen & Fishbein, 2005;Glasman & Albarracin, 2006), as well as the findings of previous research (e.g., Awad et al, 2005;Ellis et al, 2002;Kluegel & Smith, 1983), prejudice towards Indigenous Australians was negatively correlated with bystander anti-racism intentions. Those who reported more negative attitudes toward Indigenous Australians indicated that they were less likely to intervene on their behalf when witnessing an instance of discrimination against them.…”
Section: Correlates Of Bystander Anti-racism Intentions (Aim 1)supporting
confidence: 77%
“…Because of the rationalize racial inequalities (2014: 180). Empirical research supports a connection between high CBRI and greater modern racism (Awad, Cokley, & Ravitch 2005). double bind that marginalized persons face, the epistemically exploitative conditions under which the dominantly situated extract their labor are coercive. Default skeptical responses from the privileged discredit and erase the epistemic resources of the marginalized and create demand for even more unrecognized labor.…”
Section: Discussionmentioning
confidence: 93%
“…The impact of this active ignorance is not harmless. Research on color-evasive racism shows a growing body of evidence that establishes a connection between higher levels of color-evasion and power-evasion and greater demonstration of modern racist attitudes (Awad, Cokley, & Ravitch 2005). Among whites, attempting to avoid acknowledging the race of others, for instance, results in increased demonstrations of racial intolerance (Apfelbaum, Pauker, Ambady, Sommers, & Norton 2008;Norton, Sommers, Apfelbaum, Pura, & Ariely 2006).…”
Section: Idealizations Ideal Theory and Active Ignorancementioning
confidence: 99%